Domestic Violence and Mental Health Among Working and Non-Working Women - Farooq, Sana; Shaheen, Aneela; Abbas, Saleem (Dialogue Social Science Review (DSSR), 2025)
This study investigated the relationship between domestic violence and mental health among working and non-working women in Faisalabad. The correlational research design was used, and a sample of 200 women was selected through purposive sampling. Participants completed a demographic questionnaire, the Depression Anxiety Stress Scale (DASS-21), and the Domestic Violence Questionnaire. Data were analyzed using SPSS version 26. The findings revealed a significant positive correlation between domestic violence and mental health (depression, anxiety, and stress) in both working and non-working women. Regression analysis identified domestic violence as a strong predictor of mental health issues across both groups. However, t-test analysis indicated no significant difference in domestic violence and mental health outcomes between working and non-working women. These results underscore the profound impact of domestic violence on women's mental health, irrespective of employment status. The study highlights the need for heightened public awareness, policy intervention, and healthcare support tailored to the needs of women affected by domestic violence. The findings can inform the development and enhancement of intervention programs and support services for women experiencing domestic violence.